Music as a Linguistic Bridge: A Qualitative Study on Song-Mediated Grammar Acquisition in Maluku, Indonesia - Wenssy Steva Nussy (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the role of early and sustained exposure to English-language music in the natural acquisition of English grammar among Indonesian learners with mixed-age backgrounds. It explores music as a primary source of comprehensible input in a context with limited formal instructional resources. A qualitative case study approach was employed, involving eleven participants from Ambon and Dobo, Indonesia, including the author, with ages ranging from 12 to adulthood. Data collection included analysis of participants' original social media captions , focusing on specific grammatical structures such as verb tense and article usage, and semi-structured interviews exploring their histories of music exposure. This approach provided a source of authentic, unprompted language data to complement self-reported experiences. All participants demonstrated a strong, intuitive command of English grammar in unprompted writing. This competence was unanimously attributed to long-term, intergenerational engagement with English music, which provided extensive, repetitive input that allowed for the internalization of grammatical patterns. The findings suggest that music can serve as a powerful, motivating, and accessible bridge for English grammar acquisition for learners of various ages, offering a model for informal language learning. Supporting the principles of Krashen's Input Hypothesis, this study highlights the potential of leveraging music as a key pedagogical tool to supplement formal language instruction.